65.6k views
1 vote
5(-6-3d)=3(8+7d)(if there is no solution,type in ''no solution'')d= Answer

User Asaf David
by
4.9k points

2 Answers

1 vote

Answer:

d = -1.5

Explanation:

5 (- 6 - 3d) = 3 (8 + 7d)

- 30 - 15d = 24 + 21d

- 15d - 21d = 24 + 30

- 36d = 54

- d = 54/36

- d = 1.5

d = -1.5

User Sixstatesaway
by
5.5k points
2 votes

In this question, you're solving for d.

Solve for d:

5(-6 - 3d) = 3(8+7d)

Use the distributive property:

-30 - 15d = 3(8+7d)

-30 - 15d = 24 + 21d

Add 30 to both sides:

-15d = 54 + 21d

Subtract 21d from both sides

-36d = 54

Divide both sides by -36

d = -3/2

Answer:

d = -3/2 or -1.5

User Narkha
by
5.3k points